Formação permanente de professores em situação de trabalho: valorização dos saberes docentes - Alves, Cristovam da Silva (2006)
This research based its analysis on the speeches, depositions and notes taken during the implementation of a teachers training project in their working time. The aim was to identify training approaches that take into account the authorship of the involved parties, based mainly on their contexts, background, culture and representations, motivating them to acquire the way of doing it, overcoming difficulties, and sharing the existing practices in an emancipating perspective. This project chose to apply the cooperative-intervention, method based on the studies of Fals Borda (1981), Pimenta (2005), Pimenta e Moura (2000), Thiolent (1994) e Zeichner (1998), undertaking the individuals to an authorship process, which confirms or guides priorities and pathways of analysis, with the implementation of educational policies in the background, in this specific case, the organization of education in cycles. We chose to work with three institutions of the Rede Oficial de Ensino do Município de São Paulo (Official Educational System of the City of São Paulo), selected under the following criteria: distance; the availability of the individuals who were willing to undertake the study projects; and having all the ages of the elementary school. The data collected along the formation project were analyzed through the view of social psychology, taking as reference the sabers docents (TARDIF) and habitus (BOURDIEU), undertaking this information to analysis under the following categories: professional knowledge , pedagogical knowledge , disciplinary knowledge , content knowledge and experience knowledge . Besides defining the training approaches that make teachers able to switch from the social actor position to become authors of their own training paths, we reached the conclusion that the experience knowledge usually changes in being-teacher and becoming-teacher